Performance Analysis Of Civil Servants At The Department Of Education, Youth And Sport, Mamuju Regency, West Sulawesi - Muhtar Muhtar; Andi Agustang (Universitas of Muhammadiyah Makassar, 2022)
This study aims to describe: (1) the performance of civil servants Office of Education Youth and Sports Department (Dikpora) in terms of managerial ability, the ability of responsiveness, accountability, and discipline of civil servants work, and (2) the factors others that affect the performance of civil servants of Education Youth and Sports Department Mamuju Service office. The research method used is the survey method. The population of this study is all civil servants of Education Youth, and Sports Department Mamuju serves as the research sample of 42 people. To obtain data about managerial ability, the ability of responsiveness, accountability, and employee discipline obtained by using questionnaires and supported by interviews and observations, while data on other factors that affect the performance of civil servants is obtained by using the interview guide. The questionnaire used previously been tested and declared valid and reliable. The validity test with N = 27 and 0.05 confidence level obtained a value of r-table 0.381. In the test reliability coefficient of 0.948 was obtained. All the data obtained using the questionnaire were analyzed using quantitative descriptive statistics, while data obtained by interview as described by descriptive qualitative research supporting data. Results showed that (1) managerial skills of civil servants by 57.14 percent in the medium category, (2) the ability of the responsiveness of 59.53 percent in the medium category, (3) accountability of 69.05 in the high category, (4) work discipline of 66.67 percent in the medium category, and (5) the performance of civil servants by 54.76 percent in the medium category. As for other factors that affect the performance of civil servants: (1) is a factor that supports the civil service work experience, skill factors, and education level employees, (2) that inhibits the factor of employee work culture.Penelitian ini bertujuan memberikan gambaran mengenai: (1) kinerja pegawai negeri sipil (PNS) kantor Dinas Pendidikan Pemuda dan Olahraga (Dikpora) ditinjau dari kemampuan manajerial, kemampuan responsivitas, akuntabilitas, dan disiplin kerja PNS, serta (2) faktor-faktor lain yang mempengaruhi kinerja PNS kantor Dinas Dikpora Kabupaten Mamuju. Metode penelitian yang digunakan adalah metode survei sedangkan populasi penelitian ini adalah seluruh PNS Dinas Dikpora Kabupaten Mamuju dijadikan sebagai sampel penelitian yaitu 42 orang. Untuk memperoleh data mengenai kemampuan manajerial, kemampuan responsivitas, akuntabilitas, dan disiplin kerja pegawai diperoleh dengan menggunakan kuesioner dan didukung dengan wawancara dan observasi, sedangkan data mengenai faktor-faktor lain yang mempengaruhi kinerja PNS diperoleh dengan menggunakan pedoman wawancara. Kuesioner yang digunakan sebelumnya telah diuji cobakan dan dinyatakan valid dan reliabel. Pada uji validitas dengan N=27 dan taraf kepercayaan 0,05 didapat nilai r-tabel 0,381. Pada uji reliabilitas didapat koefisien sebesar 0,948. Seluruh data yang diperoleh dengan menggunakan kuesioner dianalisis dengan menggunakan statistik deskriptif kuantitaif, sedangkan data yang diperoleh dengan wawancara diuraikan dengan deskriptif kualitatif sebagai data pendukung penelitian.Hasil penelitian menunjukkan bahwa (1) kemampuan manajerial PNS sebesar 57,14 persen dalam kategori sedang, (2) kemampuan responsivitas sebesar 59,53 persen dalam kategori sedang, (3) akuntabilitas sebesar 69,05 dalam kategori tinggi, (4) disiplin kerja sebesar 66,67 persen dalam kategori sedang, dan (5) kinerja PNS sebesar 54,76 persen dalam kategori sedang. Adapun faktor-faktor lain yang mempengaruhi kinerja PNS: (1) yang mendukung adalah faktor pengalaman kerja PNS, faktor kecakapan, dan tingkat pendidikan pegawai, (2) yang menghambat adalah faktor budaya kerja pegawai.